IDENTIFICATION OF CYCLAMATE ON BRANDED AND UNBRANDED BUBLE DRINK IN DENPASAR CITY - Ayu Saka Laksmita W; Ni Putu Widayanti; Desak Putu Risky VA (Poltekkes Kemenkes Semarang, 2021)
Bubble drink is a drink that is on the rise at this time. This drink is liked by many people Bubble drink is a drink that is on the rise at this time. This drink is liked by many people because it has a sweet taste. To create a sweet taste, there are usually 2 kinds, namely natural and artificial sweeteners. Cyclamate is a type of artificial sweetener that is 30 times sweeter than sucrose. The side effects of artificial sweeteners if consumed in excessive amounts can pose a danger to human health. Among other things, it can cause urinary tract cancer and migraines. This study aims to qualitatively identify cyclamate content in bubble drinks circulating in the city of Denpasar. The total number of samples was 30 samples of bubble drinks. This research method is a descriptive study with purposive sampling, the results of the data analysis are presented in tabular form without data processing. Sample identification is done by qualitative test. The test results showed that 20 of the samples of bubble branded drinks and 10 of the samples of unbranded bubble drinks were safe from cyclamate sweetener content.